The content-based teaching style and its implication in the development of research capacity at the UPT 2014 Business Science Faculty - Catacora Lira, Luis Celerino (2016)
Objective: This study aimed to determine the type of implications that generates teaching styles with emphasis on the content development level research capacity in students from the Professional School of Business, Engineering 2014. Method: The research is descriptive and explanatory part of the premise that teaching styles of university professors have influence on the development of research capacity of students. The population consisted of students of vocational school Commercial Engineering and sample groups of students in the fourth and eighth cycle of the university. Results: This paper presents the results of the dominance of traditional teaching style in developing research capacity of university students. The research was conducted at the Professional School of Business Administration component of the Faculty of Business Studies of the Private University of Tacna. The study allowed to verify that the predominant style was the traditional university professor, characterized by giving enough emphasis to content, to explain the entire class and the teacher is the only one talking in class. On 70 the side of students, he came to see that students have failed to develop their research capacity. Conclusion: The results of the research allowed check with 95% confidence that the traditional teaching style applied university professors during the academic year 2014 had influence means on the level of development of the research capacity of students, whose effect It resulted in limited development and dissemination of scientific notes from the classroom